K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

6 tháng 3 2022

\(a,\dfrac{11}{22}-\dfrac{3}{16}.\dfrac{8}{18}+\dfrac{1}{18}=\dfrac{1}{2}-\dfrac{1}{12}+\dfrac{1}{18}=\dfrac{18}{36}-\dfrac{3}{36}+\dfrac{2}{36}=\dfrac{17}{36}\)

\(b,\dfrac{5}{7}+\dfrac{3}{7}:4-\dfrac{8}{9}.\dfrac{-3}{4}=\dfrac{5}{7}+\dfrac{3}{7}.\dfrac{1}{4}-\dfrac{-2}{3}=\dfrac{5}{7}+\dfrac{3}{28}+\dfrac{2}{3}=\dfrac{60}{84}+\dfrac{9}{84}+\dfrac{56}{84}=\dfrac{125}{84}\)

2:

a: 2/9-x=-5/9

=>x=2/9+5/9=7/9

b: x-7/13=1/2

=>x=1/2+7/13=27/26

 

12 tháng 2

câu a

\(\dfrac{7}{4}+\dfrac{3}{2}+\dfrac{-9}{16}\\ =\dfrac{28}{16}+\dfrac{24}{16}-\dfrac{9}{16}=\dfrac{43}{16}\)

câu b

\(-\dfrac{2}{7}+\dfrac{3}{5}+\dfrac{9}{7}+\dfrac{-18}{5}\\ =-\dfrac{10}{35}+\dfrac{21}{35}+\dfrac{45}{35}-\dfrac{126}{35}\\ =-\dfrac{70}{35}=-2\)

câu c

\(-\dfrac{5}{13}+\dfrac{11}{10}-\dfrac{-9}{10}+\dfrac{-8}{13}\\ =-\dfrac{5}{13}+\dfrac{11}{10}+\dfrac{9}{10}-\dfrac{8}{13}\\ =-\dfrac{50}{130}+\dfrac{143}{130}+\dfrac{117}{130}-\dfrac{80}{130}\\ =\dfrac{130}{130}=1\)

bài 2

câu a

\(\dfrac{2}{9}-x=-\dfrac{5}{9}\\ x=\dfrac{2}{9}-\dfrac{-5}{9}\\ x=\dfrac{7}{9}\)

câu b

\(x+\dfrac{-7}{13}=\dfrac{1}{2}\\ x=\dfrac{1}{2}-\dfrac{-7}{13}\\ x=\dfrac{13}{26}+\dfrac{14}{26}\\ x=\dfrac{17}{26}\)

a: 4/9+3/7=28/63+27/63=55/63

3/4+7/24=18/24+7/24=25/24

1/3+2/9+4/27=9/27+6/27+4/27=19/27

b: 5/6-3/8=20/24-9/24=11/24

7/15-11/30=14/30-11/30=3/30=1/10

2/3+1/6-7/12

=8/12+2/12-7/12

=3/12=1/4

c: 18/25*15/6=15/25*18/6=3*3/5=9/5

30/49:6/7=30/49*7/6=210/294=5/7

1/2*3/4:6/5=3/8*5/6=15/48=5/16

d: 8*3/5:12/5=24/5*5/12=2

4:9/5:10/3=4*5/9*3/10=2/3

a: \(=\left(\dfrac{3}{17}+\dfrac{14}{17}\right)+\left(\dfrac{-5}{13}-\dfrac{8}{13}\right)+\left(\dfrac{-18}{35}-\dfrac{17}{35}\right)\)

=1-1-1

=-1

b: \(=\dfrac{-3}{8}\left(\dfrac{1}{6}+\dfrac{5}{6}\right)+\dfrac{-5}{8}=\dfrac{-3}{8}-\dfrac{5}{8}=-1\)

c: \(=\dfrac{4}{4}\cdot\dfrac{5}{15}\cdot\dfrac{11}{11}=\dfrac{1}{3}\)

30 tháng 5 2022

a)\(=\left(-\dfrac{5}{13}+\dfrac{-8}{13}\right)+\left(-\dfrac{18}{35}-\dfrac{17}{35}\right)+\left(\dfrac{3}{14}+\dfrac{14}{17}\right)=-1-1+1=-1\)

 

b)\(=\dfrac{-3}{8}.\left(\dfrac{1}{6}+\dfrac{5}{6}\right)-\dfrac{10}{16}=-\dfrac{3}{8}.1-\dfrac{10}{16}=-\dfrac{6}{16}-\dfrac{10}{16}=-\dfrac{16}{16}=-1\)

c)\(\dfrac{-4.5.11}{11.5.3.-4}=\dfrac{1}{3}\)

28 tháng 10 2023

\(\dfrac{2}{5}+\dfrac{1}{5}=\dfrac{2+1}{5}=\dfrac{3}{5}\)

\(\dfrac{2}{3}+\dfrac{5}{3}=\dfrac{2+5}{3}=\dfrac{7}{3}\)

\(\dfrac{3}{8}+\dfrac{4}{8}=\dfrac{3+4}{8}=\dfrac{7}{8}\)

\(\dfrac{6}{9}+\dfrac{2}{9}=\dfrac{6+2}{9}=\dfrac{8}{9}\)

\(\dfrac{12}{18}+\dfrac{7}{18}=\dfrac{12+7}{18}=\dfrac{19}{18}\)

\(\dfrac{7}{4}+\dfrac{2}{4}=\dfrac{7+2}{4}=\dfrac{9}{4}\)

a) Ta có: \(\dfrac{5}{8}+\dfrac{3}{17}+\dfrac{4}{18}+\dfrac{20}{-17}+\dfrac{-2}{9}+\dfrac{21}{56}\)

\(=\left(\dfrac{3}{17}-\dfrac{20}{17}\right)+\left(\dfrac{2}{9}-\dfrac{2}{9}\right)+\left(\dfrac{5}{8}+\dfrac{3}{8}\right)\)

\(=-1+1=0\)

b) Ta có: \(\left(\dfrac{9}{16}+\dfrac{8}{-27}\right)+\left(1+\dfrac{7}{16}+\dfrac{-19}{27}\right)\)

\(=\left(\dfrac{9}{16}+\dfrac{7}{16}\right)+\left(\dfrac{-8}{27}-\dfrac{19}{27}\right)+1\)

=1-1+1=1

 

e: \(D=\dfrac{-10}{12}-\dfrac{7}{12}-\dfrac{4}{12}=\dfrac{-21}{12}=-\dfrac{7}{4}\)

f: \(F=\dfrac{-27}{36}+\dfrac{12}{36}+\dfrac{10}{36}=\dfrac{-5}{36}\)

g: \(G=\dfrac{209}{99}+\dfrac{36}{99}+\dfrac{66}{99}=\dfrac{311}{99}\)

h: \(H=\dfrac{10}{24}-\dfrac{42}{24}+\dfrac{3}{24}=-\dfrac{29}{24}\)

25 tháng 1 2022

\(D=\dfrac{-5}{6}+\dfrac{-7}{12}-\dfrac{1}{3}=-\dfrac{7}{4}\)

\(F=\dfrac{-3}{4}+\dfrac{1}{3}-\dfrac{-5}{18}=-\dfrac{5}{36}\)

\(G=\dfrac{19}{9}-\dfrac{-4}{11}+\dfrac{2}{3}=\dfrac{311}{99}\)

\(H=\dfrac{5}{12}+\dfrac{-7}{4}-\dfrac{1}{-8}=-\dfrac{29}{24}\)

10 tháng 3 2021

Câu 1:

\(-\dfrac{5}{7}\cdot\dfrac{7}{-45}=\dfrac{1}{9}\) ; \(-\dfrac{3}{10}\cdot-30=9\) ; \(-12\cdot-\dfrac{2}{36}=\dfrac{2}{3}\)

Caau2;3;4;5,... tự bấm máy tính là ra

 

23 tháng 8 2023

a) \(\dfrac{4}{7}< \dfrac{6}{7}\)

\(\dfrac{15}{23}>\dfrac{12}{23}\)

\(\dfrac{45}{60}=\dfrac{3}{4}\)

b) \(\dfrac{8}{9}>\dfrac{11}{18}\)

\(\dfrac{13}{18}>\dfrac{2}{3}\)

\(\dfrac{27}{25}>1\)

29 tháng 10 2023

\(\dfrac{1}{2}-\dfrac{3}{8}=\dfrac{4}{2\times4}-\dfrac{3}{8}=\dfrac{4}{8}-\dfrac{3}{8}=\dfrac{1}{8}\)

\(\dfrac{4}{3}-\dfrac{8}{15}=\dfrac{4\times5}{3\times5}-\dfrac{8}{15}=\dfrac{20}{15}-\dfrac{8}{15}=\dfrac{12}{15}=\dfrac{4}{5}\)

\(\dfrac{5}{6}-\dfrac{7}{12}=\dfrac{5\times2}{6\times2}-\dfrac{7}{12}=\dfrac{10}{12}-\dfrac{7}{12}=\dfrac{3}{12}=\dfrac{1}{4}\)

\(\dfrac{11}{4}-\dfrac{9}{8}=\dfrac{11\times2}{4\times2}-\dfrac{9}{8}=\dfrac{22}{8}-\dfrac{9}{8}=\dfrac{13}{8}\)

\(\dfrac{17}{16}-\dfrac{3}{4}=\dfrac{17}{16}-\dfrac{3\times4}{4\times4}=\dfrac{17}{16}-\dfrac{12}{16}=\dfrac{5}{16}\)

\(\dfrac{31}{36}-\dfrac{5}{6}=\dfrac{31}{36}-\dfrac{5\times6}{6\times6}=\dfrac{31}{36}-\dfrac{30}{36}=\dfrac{1}{36}\)